If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 * 2 + -1y = -6 Multiply 2 * 2 4 + -1y = -6 Solving 4 + -1y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1y = -6 + -4 Combine like terms: 4 + -4 = 0 0 + -1y = -6 + -4 -1y = -6 + -4 Combine like terms: -6 + -4 = -10 -1y = -10 Divide each side by '-1'. y = 10 Simplifying y = 10
| x-2y+9=0 | | X^2+12x=x-24 | | -9=x/4-7 | | 4=z/9.5 | | 2*2-6=a | | 2*2-6=-6 | | (-4)(7)= | | 5=2-y | | 2y+1=0 | | 0=-3-1y | | (-6)(-7)= | | 2x-8-x=-6 | | 0y-1=1 | | 2x=5x-42 | | 6=16-2y | | -1.1x-2.5=-2.7 | | w=(5/6)^3 | | 0=y-2 | | 21/2-11/3*11/4 | | -34+27= | | 36+x=180 | | 25.2t-24.5=300.5 | | 0.6x-3=2.25 | | 5-19= | | graphy-3x=0 | | 2-1y=0 | | 9(-8)= | | 5x-7/18=-7/12 | | 2=-2y-0 | | 3w^(-4/5)=1/2 | | (4x)(3x+5)= | | 6xy=18 |